Chemokine Expression in Human Astrocytes in Response to Shiga Toxin 2 - Naomi Kioka; Koichi Minami; Akira Tamura; Norishige Yoshikawa (International Journal of Inflammation)
Infection with Shiga toxin- (Stx-) producing Escherichia coli can lead to hemolytic uremic syndrome (HUS). Approximately, 30% of patients with HUS suffer from complications in the central nervous system (CNS), which is an important determinant of mortality in such patients. Autopsy shows mostly edema and hypoxic-ischemic changes in the CNS, often with microhemorrhages. It has been suggested that Stx-induced damage to human brain endothelial cells, which are essential constituents of the blood-brain barrier, plays a crucial role in the development of the CNS complications. However, it is unclear whether Stx affects brain neuroglial cells. In the present study, we investigated the direct involvement of Stx in the inflammatory responses of human astrocytes (HASTs) treated with Stx. Immunohistochemistry and real-time PCR revealed that the expression of globotriaosylceramide (Gb3), the receptor for Stx2, and Gb3 synthase (GalT6) in HASTs was increased by interleukin-1β (IL-1β). Expression of both interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) mRNA in HASTs was significantly upregulated by Stx2. These results suggest that Stx2 induces inflammatory responses, particularly through expression of chemokines, in HASTs expressing Gb3 and may, thus, affect brain glial cells, playing a key role in the pathogenesis of CNS manifestations associated with HUS.